2016
DOI: 10.18632/oncotarget.11779
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos over-expression promotes radioresistance and predicts poor prognosis in malignant glioma

Abstract: c-Fos is a major component of activator protein (AP)-1 complex. It has been implicated in cell differentiation, proliferation, angiogenesis, invasion, and metastasis. To investigate the role of c-Fos in glioma radiosensitivity and to understand the underlying molecular mechanisms, we downregulated c-Fos gene expression by lentivirus-mediated shRNA in glioma cell lines and subsequently analyzed the radiosensitivity, DNA damage repair capacity, and cell cycle distribution. Finally, we explored its prognostic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Although TMZ is considered to be one of the most effective chemotherapeutic agents to prolong GBM patient survival [2] , these SOC treatments, including TMZ, have not provided any long-term survival, and reoccurrence is very common. The recurrence for high-grade gliomas, particularly GBM, is due to difficulty in achieving a gross surgical section coupled with resistance to chemo- (mainly TMZ) [3] , [4] and radiotherapies [5] , [6] . Glioma-initiating cells that have stem-like properties have been linked with resistance to therapy and progression [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Although TMZ is considered to be one of the most effective chemotherapeutic agents to prolong GBM patient survival [2] , these SOC treatments, including TMZ, have not provided any long-term survival, and reoccurrence is very common. The recurrence for high-grade gliomas, particularly GBM, is due to difficulty in achieving a gross surgical section coupled with resistance to chemo- (mainly TMZ) [3] , [4] and radiotherapies [5] , [6] . Glioma-initiating cells that have stem-like properties have been linked with resistance to therapy and progression [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, overexpression of c-Jun and c-Fos also promoted the malignant transformation of cells ( 19 ). Previous investigations revealed that silencing of c-Fos sensitized glioma cells to radiation and c-Fos overexpression was correlated with poor prognosis in malignant glioma patients ( 20 ). c-Fos transcriptionally controled MMP10 and S100A15 expression in keratinocytes in skin squamous cell carcinoma, promoting epidermal hyperplasia ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…c-FOS, as a major component of activator protein (AP)-1 complex, has been involved in cell differentiation, proliferation, angiogenesis, invasion, and metastasis [45,46]. Here, we found that c-FOS was an important target gene positively regulated by miR-744, which mediated the promotion of miR-744 on the malignant phenotype of NSCLC cells.…”
Section: Discussionmentioning
confidence: 87%